Structural changes in the extracellular loop 2 of the murine KCC2 potassium chloride cotransporter modulate ion transport - Hartmann, Anna-Maria (J Biol Chem, 2021)
K(+)–Cl(−) cotransporters (KCCs) play important roles in physiological processes such as inhibitory neurotransmission and cell-volume regulation. KCCs exhibit significant variations in K(+) affinities, yet recent atomic structures demonstrated that K(+)- and Cl(−)-binding sites are highly conserved, raising the question of whether additional structural elements may contribute to ion coordination. The termini and the large extracellular domain (ECD) of KCCs exhibit only low sequence identity and were already discussed as modulators of transport activity. Here, we used the extracellular loop 2 (EL2) that links transmembrane helices (TMs) 3 and 4, as a mechanism to modulate ECD folding. We compared consequences of point mutations in the K(+)-binding site on the function of WT KCC2 and in a KCC2 variant, in which EL2 was structurally altered by insertion of a IFYPYDVPDYAGYPYDVPDYAGSYPYDVPDYAAHAAA (3xHA) tag (36 amino acids). In WT KCC2, individual mutations of five residues in the K(+)-binding site resulted in a 2- to 3-fold decreased transport rate. However, the same mutations in the KCC2 variant with EL2 structurally altered by insertion of a 3xHA tag had no effect on transport activity. Homology models of mouse KCC2 with the 3xHA tag inserted into EL2 using ab initio prediction were generated. The models suggest subtle conformational changes occur in the ECD upon EL2 modification. These data suggest that a conformational change in the ECD, for example, by interaction with EL2, might be an elegant way to modulate the K(+) affinity of the different isoforms in the KCC subfamily.